2016 54th Annual Allerton Conference on Communication, Control, and Computing (Allerton) 2016
DOI: 10.1109/allerton.2016.7852261
|View full text |Cite
|
Sign up to set email alerts
|

Linear regression with an unknown permutation: Statistical and computational limits

Abstract: Consider a noisy linear observation model with an unknown permutation, based on observing y = Π * Ax * + w, where x * ∈ R d is an unknown vector, Π * is an unknown n × n permutation matrix, and w ∈ R n is additive Gaussian noise. We analyze the problem of permutation recovery in a random design setting in which the entries of the matrix A are drawn i.i.d. from a standard Gaussian distribution, and establish sharp conditions on the SNR, sample size n, and dimension d under which Π * is exactly and approximately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 31 publications
3
62
0
Order By: Relevance
“…It can be shown that with σ 2 w being zero, equation (13) holds, which is consistent with the results obtained in [9].…”
Section: Holds Then the Summaries Of Sensor's Observationsỹ Are Sortsupporting
confidence: 90%
See 4 more Smart Citations
“…It can be shown that with σ 2 w being zero, equation (13) holds, which is consistent with the results obtained in [9].…”
Section: Holds Then the Summaries Of Sensor's Observationsỹ Are Sortsupporting
confidence: 90%
“…Remark 1 For the ML estimation problem (6) with σ 2 w = 0, a polynomial time algorithm is provided [9]. It can be shown that with σ 2 w being zero, equation (13) holds, which is consistent with the results obtained in [9].…”
Section: Holds Then the Summaries Of Sensor's Observationsỹ Are Sortsupporting
confidence: 78%
See 3 more Smart Citations